(untitled) (Nigerian Journal of Technology, 2021)
The performance evaluation of Mixed-Mode Passive Solar Dryer for drying codfish (Gadusmorhua) was conducted. The dryer is comprised of among other things, materials for sensible heat storage to discharge heat during the off-sunshine period. The drying chamber is integrated with a suction device to aid the convective airflow to avoid reversible reaction during the discharge of accumulated moisture. The solar dryer was evaluated with fresh codfish samples at the initial moisture content of 79% (wet basis). The samples were divided into sets. A set was treated with Moringa Oleifera and the second set with salt solution. The results showed that, for Moringa and salt treatments, the moisture content of the codfish was reduced to 16.03% and 13.33% (wet basis) respectively using the solar dryer while 19.55% and 13.46% respectively under ambient condition in six days. Laboratory tests showed that bacteria and fungi count for Moringa and salt treated codfish under solar dryer were below consumable limits.